2021
DOI: 10.1371/journal.pone.0249588
|View full text |Cite
|
Sign up to set email alerts
|

Preventing COVID-19 spread in closed facilities by regular testing of employees—An efficient intervention in long-term care facilities and prisons?

Abstract: Background Different levels of control measures were introduced to contain the global COVID-19 pandemic, many of which have been controversial, particularly the comprehensive use of diagnostic tests. Regular testing of high-risk individuals (pre-existing conditions, older than 60 years of age) has been suggested by public health authorities. The WHO suggested the use of routine screening of residents, employees, and visitors of long-term care facilities (LTCF) to protect the resident risk group. Similar sugges… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 46 publications
(58 reference statements)
1
24
1
Order By: Relevance
“…One recent study found that the frequency of employee testing, supplemented with other infection control measures, plays a key role in reducing the number of cases and deaths in long-term care facilities. [ 91 ] The findings suggested that frequent testing of employees (i.e., daily) using good quality antigen rapid tests is more effective than less frequent testing (i.e., once every 5 days) using good quality PCR tests. Similarly, a decision analytical modeling study based on simulated nursing home residents and staffs found that antigen tests performed better than PCR tests in reducing transmission at the same testing frequency due to rapid turn-around, and that daily antigen rapid testing was the most effective testing strategy in the reduction in infections.…”
Section: Societal Impactmentioning
confidence: 99%
“…One recent study found that the frequency of employee testing, supplemented with other infection control measures, plays a key role in reducing the number of cases and deaths in long-term care facilities. [ 91 ] The findings suggested that frequent testing of employees (i.e., daily) using good quality antigen rapid tests is more effective than less frequent testing (i.e., once every 5 days) using good quality PCR tests. Similarly, a decision analytical modeling study based on simulated nursing home residents and staffs found that antigen tests performed better than PCR tests in reducing transmission at the same testing frequency due to rapid turn-around, and that daily antigen rapid testing was the most effective testing strategy in the reduction in infections.…”
Section: Societal Impactmentioning
confidence: 99%
“…As a consequence the waiting times to progress between compartments are Erlang-distributed (cf. [32][33][34][35]).…”
Section: Course Of the Diseasementioning
confidence: 99%
“…Antigen tests originally had low sensitivity compared to nucleic examinations [ 3 ]. Their diagnostic performance has improved over time [ 4 ], and previous research has found them beneficial for screening purposes [ 5 ] or in low-resource settings [ 6 ]. Advantages of antigen tests include the ability to analyze multiple samples simultaneously, the lack of a need for special equipment, and the fast turnaround time (TAT).…”
Section: Introductionmentioning
confidence: 99%